(untitled) (Discourse of Law and Administration, 2023)
The article deals with recent, repeated Rule of Law violations in Poland and Hungary and how the EU has dealt with them, or ought to deal with them in the future. Specific measures are recommended particularly in the budget process, where the new requirement of “conditionality” should be made use of. The impact of the war in Ukraine and the different attitudes of Poland and Hungary towards the Russian invasion on the rule of law crisis is taken into account.